Acquiring a Secondary Language - Rafah Mazban Badan - Fatima Karimi - Farzana Mahdi Zarfashani ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Second languiage acquiisitioin has sophisticated into an indepeindent boundary interdisciplinary. It includes linguistics, psychology, sociology, pedagogy and other diisciplines. Following more than 30 years of development, it has gradually developed its theoretical framework and created a collection of reliable research techniques.The study of second language learning has grown considerably in recent years, and several new hypotheses have continued to surface. Based on the review of the development process of second language acquisition research. This article focuises on the best developments in foreign second language acquisition research, involving the internal and external factors of learners in the interlanguage representation language cognitive mechanism correlation theory and learner corpus research. At the same time, the article also reviews the current status of second language acquisition research, points out several major problems in it, and discusses how to promote second language acquisition.  The article assists that the study of secoind language acquisition baised on the forefront of subject development; take the road of reference and innovation, and in-depth study of foreign language learning.